An unusual case of malignant cystosarcoma phyllodes of the breast - De Luca, Laurival A. [UNESP]; Traiman, Paulo [UNESP]; Bacchi, Carlos E. [UNESP] (Elsevier, 1986)
A unusually large tumor of the left breast diagnosed as a cystosarcoma phyllodes with multiple malignant sarcomatous changes of the stroma, consisting of liposarcoma, myxoid fibrosarcoma, anaplastic, and giant cell sarcoma is described. The weight of 6200 g (13.5 lb) seems to be the largest so far presented in the literature reviewed by the authors. © 1986.
Keywords: breast; breast cancer; case report; cystosarcoma phylloides; diagnosis; human; priority journal; therapy; Breast Neoplasms; Case Report; Female; Human; Phyllodes Tumor